A study of the tourism industry in East Taiwan - SU-FANG WU; CHUN-CHIEH YANG; TIAN-CHEN CHANG; SHAO-CHI HSU (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper discusses potential strategies for growing the tourism sector in the area. We use Hualien County as an illustration. Hualien County is a region in East Taiwan known for its breathtaking scenery and diverse eco-friendly landscape. A crucial issue is how to effectively boost the regional economy and the tourism sector. This issue is the main focus of the paper.Methodology: Our qualitative research is based on archival analysis of reports about Hualien’s most popular tourist spot and on participant observation. To promote tourism, we conducted a SWOT analysis of the available literature.Findings: We discovered that the local government should coordinate the culture of festive activities and provide clear publicity for the events. The media should be used in the management of the tourism industry. Cooperation between the government and businesses should enhance the growth of the tourism industry.Implications/Novelty: The implication is that there may still be unresolved conflicts between the quickening pace of tourism growth and the protection of the area’s natural beauty.